A comparative assessment of RNF38 and P53 genes expression in the sperm samples obtained from males with normozoospermia and asthenospermia: A case-control study - Alireza Alizadeh; Sina Mirzaahmadi; Golnaz Asaadi Tehrani; Neda Jabbara (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Infertility is considered as a common problem appears in about 10-12% of couples in their reproductive ages. Ring finger protein 38 (RNF38) gene is a ubiquitin-protein ligase that can regulate Protein 53 (P53) and affect cellular motility. Objective: Considering the role of P53 on cellular motility and RNF38 on the regulation of P53, the present study aimed to assess the difference between RNF38 and P53 genes expression in normozoospermic and asthenospermic samples as a diagnostic biomarker in males. Materials and Methods: The present study was conducted among 21 asthenospermicsand 63 healthy individuals. First, the real-time polymerase chain reaction technique was applied to measure the expression level of the P53 and RNF38 genes extracted from sperm samples, and the glyceraldehyde-3phosphate dehydrogenase gene was selected as the reference gene. Results: An increase and a decrease occurred in the level of P53 and RNF38 genes expressions in asthenospermic and normozoospermic samples, respectively. In addition, a significant difference was observed between increasing P53 gene expression (p < 0.001), reducing RNF38 one, and decreasing sperm motility (p < 0.001) in asthenospermic cells compared to that of normozoospermic ones. Conclusion: Based on the results, an increase in the expression of the P53 gene and a decrease in the expression of the RNF38 gene had a significant relationship with asthenospermia in men. Therefore, it is expected that an effective step should be adopted to diagnose the asthenospermia expression pattern by using these results.